To pack or not to pack- A Randomized Clinical Trial comparing the Immediate Outcomes of Packed and Non Packed abscess wounds - Bhuhan Rijal (Society of Surgeons of Nepal, 2017)
Introduction: The objective of this study was to determine if there was any benefit from routine abscess packing after incision and drainage as compared to incision and drainage alone, as there seems to be emerging literature negating this practice.